The approach to the comparative morphological analysis of spores of the Pteridaceae E. D. M. Kirchn family representatives (Pteridophyta) based on phylogenetic relationship data - A. V. Vaganov; M. V. Skaptsov; D. I. Kogtev (Проблемы ботаники Южной Сибири и Монголии, 2020)
The work presents the result of using comparative morphological analysis of spore of threesubfamilies from the family Pteridaceae E. D. M. Kirchn. (Cryptogrammoideae S. Linds., Pteridoideae C. Chr.ex Crabbe, Jermy a. Mickel, Ceratopteridoideae (J. Sm.) R. M. Tryon) by evolutionary biology method by Mesquitesoftware. This approach allows comparing in detail the standardized qualitative features of the morphology of sporeswith the data on phylogenetic relationship of representatives, which as a result helps to identify intra- and intertaxonomicgroups of relationship, to search for evolutionary connections, to obtain new knowledge for solving problems in ferntaxonomy. Obtained data allow supplement natural classification of the Pteridaceae family.